ICARE Based Training: An Effort to Empower Teachers in Writing Action Research Classroom in Tuban District, East Java, Indonesia - fifi khoirul fitriyah; Amin Siti Maghfirotun (Community Development Journal, 2021)
Many sources mention the low quality of education in Indonesia. Through the action research classroom, gradual changes began. The essence of an action research classroom is the evaluation of learning. The benefit of this program is to improve the teacher's ability to conduct classroom action research. In addition, the mastery of writing action research classroom is also useful for increasing teacher credit scores for promotion. The target of this program is teachers in the Tuban Regency under the auspices of the Teacher Learning Center (PBG). The purpose of this activity is to improve understanding and ability to write action research classroom. The implementation method is through a series of training activities for one year using the ICARE model. The result of the activity is an increase in the teacher's understanding of the training material. In addition, the output of this activity is a report on action research classrooms. Based on the results of the activity output, the weakness of the teachers is in the literature review process and writing references. The teacher's advantage is creating innovative learning. The recommendation for further community service activities is a need for assistance to improve the ability to find literature reviews for teachers.